Physics Students' Perceptions of Microlearning: A New Approach in Education - Astuti, Irnin Agustina Dwi; Japar, Muhammad; Wibawa, Basuki (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
The implementation of microlearning strategies in physics education is crucial and relevant in today's digital era. Microlearning, with its focused and concise approach, is believed to enhance student motivation and understanding. The purpose of this study is to explore physics students' perceptions of microlearning strategies and their impact on their learning experiences. The research method used in this study is descriptive qualitative. Data analysis was conducted using descriptive statistics to identify patterns and trends in student perceptions. The results indicate that the majority of students have a positive perception of microlearning, considering it an effective method for understanding complex physics concepts. Students also reported increased motivation and engagement in the learning process. The implications of these findings suggest that integrating microlearning strategies into the physics curriculum can enhance students' learning experiences and academic outcomes. This research provides important insights for educators in designing more adaptive and responsive learning environments that meet the needs of students in the modern era.